Religion and the Global Media: Improving a Strained Relationship - Nielsen, Nancy M. (Tufts Archival Research Center, 2005)
Volume 20, Issue 1. Winter/Spring Religious leaders and the global media elite make an unlikely couple, but through increased understanding and respect they may be able to work together to stem conflicts.